Efektivitas Pelatihan Kualitas Relasi Atasan-Bawahan untuk Meningkatkan Organizational Citizenship Behaviour pada Karyawan BPR X di Makassar - Muhammad Ikhsan Baharuddin (COMSERVA, 2023)
Employees who have organizational citizenship behavior will show concern for colleagues and are able to help other employees in developing the company, especially when employees cooperate with superiors on events in the work environment. Organizational citizenship behavior can be defined as an individual's contribution that exceeds the demands of the role in the workplace. Individuals who have high organizational citizenship behavior will be able to improve organizational performance because behavior is the lubricant of the social engine in the organization. In other words, with this behavior, social interaction in its members runs smoothly so that it can bring up positive feelings when responding to these problems. This study aims to see whether quality training between superiors and subordinates can effectively improve organizational citizenship behavior in employees. Selection of subjects using purposive sampling with characteristics, namely employees of PT. BPR X Makassar City aged 20-35 years, working for at least 5 years, and is included in the category of low organizational citizenship behavior. The research method used is a quasi-experimental method with scale as a data collection tool. The scale used in this study is the organizational citizenship behavior scale and uses quality training interventions for superior and subordinate relations. The data analysis used is an independent sample t-test and paired sample t-test data analysis technique. Analysis of the independent sample t-test showed the value of t was 11,839 with p which is 0.000 (p<0.05), the mean posttest value of the experimental group was 86.92 and the mean posttest value of the control group was 64.92, thus the organizational citizenship behavior of the experimental group was higher than that of the control group. Analysis of paired t-test samples showed a t value of -26,489 with p of 0.000 (p<0.05), a pretest mean value of 57.33 and a posttest mean of 86.92, thus organizational citizenship behavior in the experimental group after treatment was higher than before treatment. ANAVA test result with partial eta squared score of 0.871. The findings prove that quality training between superiors and subordinates is effective in improving organizational citizenship behavior in PT. BPR X Makassar City.